182k views
2 votes
Indicate a general rule for the nth term of this sequence.

-6a, -3a, 0a, 3a, 6a. . .

an = 3an + 9a
an = -3an - 9a
an = -3an + 9a
an = 3an - 9a

User Elie Asmar
by
5.3k points

2 Answers

7 votes

difference=3a

so an=-6a+(n-1)3a

=3an-9a

User Totati
by
5.3k points
3 votes

Answer:

Option D.
a_(n)=3an-9a
is the answer.

Explanation:

The given sequence is -6a, -3a, 0a, 3a, 6a...........

Since the given sequence is having a common difference d = -3a - (-6a) = -3a + 6a = 3a

Therefore, the given sequence is an arithmetic sequence.

And for an arithmetic sequence general rule or explicit formula is given by


T_(n)=a+(n-1)d

Where a = first term of the sequence

d = common difference

n = number of term which we have to find

Now we put the values from the given sequence


T_(n)=-6a+(n-1)3a


T_(n)=-6a+3an-3a


T_(n)=3an-9a

Option D.
a_(n)=3an-9a
is the answer.

User Kasheim
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.